Characterization Of Sungai Batu Ancient River System By Integrated Geophysical Technique - Andika, Fauzi (2018)
In 2007, the Centre for Global Archaeological Research (CGAR) Universiti Sains Malaysia (USM) has discovered existence historical object in Sungai Batu, Kedah. Based on excavation result, known that Sungai Batu was declare as an early civilization in Southeast Asia. This triggering archaeologist to extend the excavation site. Try and error methods by excavate random area is time consuming, failure to find buried object and can disturb the historical evidence. This study used 2-D resistivity imaging and seismic refraction methods to determine and validate the resistivity and velocity value at Sungai Batu and to identify and characterize subsurface geology and geomorphology profile Sungai Batu ancient river system.